Reading hypermedia narrative stars, 88 Constellations For Wittgenstein by David Clark. Analytical approach to Constellation 18 Cassiopeia - Nohelia Meza (Texto Digital)
This article presents an approach to analyze hypermedia discourse elements found in Cassiopeia, one of the constellations that compose 88 Constellations for Wittgenstein (To Be Played with the Left Hand) (2011) by net.art artist David Clark. Even though there are many approaches to the subject of electronic literature, there are still many unexplored e-lit works waiting to be studied that undoubtedly will raise questions about the literariness of electronic literature. This article briefly outlines issues of representation, temporality, semiotics, interaction, and manipulation on this specific constellation of the aforementioned e-lit work. Specific new media literary theories (temporal possibilities in programmed texts; temporal levels for cybertexts with narrative content; pluricode couplings, lability of digital works) have been applied to the selected corpus in order to examine the nuances and gradations of electronic textuality and literary reception. The analysis shows that the user’s manipulation and interaction with the e-lit work affect certain elements in the hypermedia narrative discourse so as to suggest new possibilities of temporal and semiotic interpretation.